Meeting the food waste challenge in higher education. Issue 6 (27th July 2018) - Ahmed, Selena; Byker Shanks, Carmen; Lewis, Martin; Leitch, Alicia; Spencer, Caitlin; Smith, Erin M.; Hess, Dani
Abstract : Purpose: Food waste represents a major sustainability challenge with environmental, economic, social and health implications. Institutions of higher education contribute to generating food waste while serving as models in championing sustainability solutions. An experiential learning project was implemented as part of two university courses in a buffet-style university dining hall with the objective to reduce food waste while building student capacity to contribute to transformational food system change. Design/methodology/approach: Partnerships were developed with university dining services. Students were trained to conduct a needs assessment in a university dining hall through food waste measurements. Students were facilitated through the process of applying baseline data on food waste to design, implement and evaluate a multi-component food waste intervention that consisted of offering reduced portion sizes, use of smaller serving utensils and educational messaging. Participant reflections were elicited to evaluate the effectiveness of the experiential learning experience. Findings: The food waste intervention led to a 17 per cent reduction in total food waste, with a large portion of waste attributed to post-consumer plate waste. While the reduction in food waste was not statistically significant, it highlights the potential for food service operations to address food waste through reduction techniques while providing students an experiential opportunity that meets multiple learning objectives including systems thinking, collaboration and motivation for leading change in the food system. Originality/value: This study highlights the opportunity of building student capacity to address sustainability challenges through an experiential learning model for reducing food waste in an institutional setting that other educators can adapt.